Recherche collaborative, analyse de l’activité et évolution des pratiques professionnelles en didactique de la grammaire - Magali Durrieu-Gardelle (Recherches en Éducation)
This contribution examines the potential link between the disciplinary consciousness of teachers and that of their cycle 3 students with regard to the discursive communities they build in grammar. We hypothesize that collaborative research helps to transform their disciplinary awareness and to objectify the issues of oral and its specificity in the classroom. We analyze the speech of two teachers during the self-confrontation at their session on the complex sentence to identify some signs of objectification and "shifts" in the declared practices.